Comparison of LS-PWM with different modulation strategies for SVC PLUS - S.A Kamran; Mao Chengxiong (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Urbanization is continuing around the world accompanied by a constantly growing demand for energy. For these reasons, new and efficient solutions for power transmission are required. To cope with these new challenges a novel SVC PLUS (Static Var Compensation SVC) for Reactive Power Compensation is designed and researched. SVC PLUS is an advanced STATCOM (Static Synchronous Compensator) with Modular Multilevel Converter (MMC) technology, also called (M-STATCOM). In this paper the M-STATCOM is simulated in PSCAD environment with 100 sub-modules per phase. Its static and dynamic characteristics are discussed. After compare and contrast different modulation schemes, harmonic contents in Level-shift sine pulse width modulation (LS-PWM) are found having least total harmonic distortions (THD) and with this modulation scheme converter can achieve more levels so it is found feasible to control the converter. The behaviour of circulating current with least ripples is also observed. In this paper, the traditional capacitor balance strategy is also modified.The viability of the MMCs as well as the effectiveness of the LS-PWM control method is confirmed by simulation. DOI: http://dx.doi.org/10.11591/telkomnika.v13i1.6821